Engineering adoptive T cell therapy to co-opt Fas ligand-mediated death signaling in ovarian cancer enhances therapeutic efficacy. Issue 3 (9th March 2022) - Anderson, Kristin G; Oda, Shannon K; Bates, Breanna M; Burnett, Madison G; Rodgers Suarez, Magdalia; Ruskin, Susan L; Greenberg, Philip D
Abstract : Background: In the USA, more than 50% of patients with ovarian cancer die within 5 years of diagnosis, highlighting the need for therapeutic innovations. Mesothelin (MSLN) is a candidate immunotherapy target; it is overexpressed by ovarian tumors and contributes to malignant/invasive phenotypes, making tumor antigen loss disadvantageous. We previously showed that MSLN-specific T cell receptor (TCR)-engineered T cells preferentially accumulate within established tumors, delay tumor growth, and significantly prolong survival in the ID8VEGF mouse model that replicates many aspects of human disease. However, T cell persistence and antitumor activity were not sustained. We therefore focused on Fas/FasL signaling that can induce activation-induced cell death, an apoptotic mechanism that regulates T cell expansion. Upregulation of FasL by tumor cells and tumor vasculature has been detected in the tumor microenvironment (TME) of human and murine ovarian cancers, can induce apoptosis in infiltrating, Fas (CD95) receptor-expressing lymphocytes, and can protect ovarian cancers from tumor-infiltrating lymphocytes. Methods: To overcome potential FasL-mediated immune evasion and enhance T cell responses, we generated an immunomodulatory fusion protein (IFP) containing the Fas extracellular binding domain fused to a 4-1BB co-stimulatory domain, rather than the natural death domain. Murine T cells were engineered to express an MSLN-specific TCR (TCR1045 ), alone or with the IFP, transferred into ID8VEGF tumor-bearing mice and evaluated for persistence, proliferation, cytokine production and efficacy. Human T cells were similarly engineered to express an MSLN-specific TCR (TCR530 ) alone or with a truncated Fas receptor or a Fas-4-1BB IFP and evaluated for cytokine production and tumor lysis. Results: Relative to murine T cells expressing only TCR1045, T cells expressing both TCR1045 and a Fas-4-1BB IFP preferentially persisted in the TME of tumor-bearing mice, with improved T cell proliferation and survival. Moreover, TCR1045 /IFP + T cells significantly prolonged survival in tumor-bearing mice, compared with TCR1045 -only T cells. Human T cells expressing TCR530 and a Fas-4-1BB IFP exhibit enhanced functional activity and viability compared with cells with only TCR530 . Conclusions: As many ovarian tumors overexpress FasL, an IFP that converts the Fas-mediated death signal into pro-survival and proliferative signals may be used to enhance engineered adoptive T cell therapy for patients.